2010
DOI: 10.1126/science.1184028
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Control of Spin Polarization

Abstract: A current drawback of spintronics is the large power that is usually required for magnetic writing, in contrast with nanoelectronics, which relies on "zero-current," gate-controlled operations. Efforts have been made to control the spin-relaxation rate, the Curie temperature, or the magnetic anisotropy with a gate voltage, but these effects are usually small and volatile. We used ferroelectric tunnel junctions with ferromagnetic electrodes to demonstrate local, large, and nonvolatile control of carrier spin po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
477
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(508 citation statements)
references
References 39 publications
18
477
1
3
Order By: Relevance
“…The TER associated with ferroelectric polarization switching has been observed experimentally in BaTiO 3 -and PbTiO 3 -based FTJs in which either La 2/3 Sr 1/3 MnO 3 or SrRuO 3 is used as one of the electrodes while the other side of the ferroelectric thin film is in contact with the tip of an atomic force microscope [24][25][26] . The predicted simultaneous TMR and TER effects 23 have also been demonstrated experimentally in La 2/3 Sr 1/3 MnO 3 /BaTiO 3 /Fe (or Co) MFTJs [27][28][29][30][31][32][33][34] . Although the majority of the work deals with low bias, the existence of TER at finite bias has been predicted based on calculations using a semiclassical approximation 19 and first-principles 35 in FTJs, and model tight-binding calculations in MFTJs 36 .…”
Section: Introductionmentioning
confidence: 78%
“…The TER associated with ferroelectric polarization switching has been observed experimentally in BaTiO 3 -and PbTiO 3 -based FTJs in which either La 2/3 Sr 1/3 MnO 3 or SrRuO 3 is used as one of the electrodes while the other side of the ferroelectric thin film is in contact with the tip of an atomic force microscope [24][25][26] . The predicted simultaneous TMR and TER effects 23 have also been demonstrated experimentally in La 2/3 Sr 1/3 MnO 3 /BaTiO 3 /Fe (or Co) MFTJs [27][28][29][30][31][32][33][34] . Although the majority of the work deals with low bias, the existence of TER at finite bias has been predicted based on calculations using a semiclassical approximation 19 and first-principles 35 in FTJs, and model tight-binding calculations in MFTJs 36 .…”
Section: Introductionmentioning
confidence: 78%
“…13 The energetic ordering of the e g orbitals on each Mn site as well as neighboring Mn sites profoundly affects the ground state magnetic properties. [14][15][16][17][18][19][20] Although structural distortions (e.g., Jahn-Teller or GdFeO 3 distortions) are common for bulk perovskite manganites, they only weakly remove orbital degeneracy. 13 With the development of epitaxial thin film growth techniques, it is possible to remove orbital degeneracy through straininduced Jahn-Teller-like distortions.…”
mentioning
confidence: 99%
“…The spin filter efficiency was strongly affected by exchange splitting of ferromagnets and the asymmetric energy potentials derived from the opposite polarizations at the interface. In 2010, Garcia et al [49] demonstrated the polarization-dependent TMR up to −17% in a (5 nm) Fe/(1 nm) BTO/ (30 nm) LSMO heterostructures at 4.2 K. Typically, spin polarization was the key parameter to control the behavior of the TMR effect [50]. The spin-polarization-dependent tunneling was very sensitive to the interfacial states of Fe/ BTO and BTO/LSMO, which could be controlled by opposite polarizations as shown in Fig.…”
Section: Charge Transfermentioning
confidence: 99%